A comparative study on the efficacy of first vs second blood culture set in the diagnosis of bacteraemia in Central Referral Hospital, Sikkim, India - Karma G. Dolma; Deepan Gautam; Kh. Pooja Devi; T. S. K. Singh (International Journal of Medical Research and Review, 2016)
Background: An important but controversial subject is the number of blood culture sets required for the diagnosis of blood stream infection (BSI) and also the use of appropriate antibiotics to treat bacteremia. This paper focuses on the need of two blood culture set in comparison to one blood culture in the diagnosis of bacteraemia.Methods: First and second sets were collected aseptically from two different sites at an interval of about one hour from all clinically suspect patients of bacteremia. The samples were processed in Bact/ALERT3D system and further identified in VITEK 2 compact.Results: Second blood culture set yielded higher rates of positive cultures (63%) than first set (37%). The common bacterial isolates were Coagulase negative Staphylococcus (CoNS) 29 (28%), followed by Staphylococcus aureus 20 (20%), Escherichia coli 13 (13%) and Klebsiella pneumonia 11(11%). Methicillin resistance was observed in 90% of S. aureus isolates. All Gram positive bacteria were found sensitive to vancomycin. In Gram-negative organisms, extended spectrum β-lactamases (ESBL) was observed in 40.5% isolates and resistance to carbapenems was found to be 37.8%.Discussion/Conclusion: In India, most hospitals routinely use single aerobic blood culture. The isolation of CoNS in blood is difficult to interpret hence, proper collection, processing, and relevant clinical information can significantly reduced the chances of contamination. Automated blood culture system can significantly shorten the length of time for isolation and identification compared to the manual techniques which takes about seven days. Resistance to antibiotics is a matter of concern that can result in ineffective treatment.